Algorithms in a nutshell - Heineman, George T.; Pollice, Gary; Selkow, Stanley, 1944- (In a nutshell (O'Reilly & Associates), 2016)
This book provides efficient code solutions in several programming languages that you can easily adapt to a specific project. Each major algorithm is presented in the style of a design pattern that includes information to help you understand why and when the algorithm is appropriate--